2017
DOI: 10.12740/pp/75739
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the relationship between orthorexia and vegetarianism using the BOT (Bratman Test for Orthorexia)

Abstract: Very few studies can be found on the relationship between orthorexia nervosa and vegetarianism. Some scientists believe that vegetarians are particularly prone to orthorexia nervosa. In addition, it has been suggested by other researchers that vegetarianism can be used to mask eating disorders, as it allows these affected individuals to avoid certain products or situations related to food. The direction of cause and effect cannot be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 13 publications
6
31
1
7
Order By: Relevance
“…Our results are consistent with previous research using the same questionnaire (EHQ) [20,33]. Other studies (using another methods) have also indicated that individuals following a vegetarian diet reported more orthorexic behaviors than those who follow an omnivorous diet [17,34,35]. It is worth pointing out that both vegetarian diet and orthorexia nervosa share some similarities: specific food selection (consuming healthy and organic food), making eating-related issues an important area of one's own life, focusing on quality of food intake, reduction of food intake according to specific nutrition rules, nutrition rules specifying which foods are "allowed" and which are "forbidden, rigid food rules and an inability to remain flexible in one's eating habits" [20].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with previous research using the same questionnaire (EHQ) [20,33]. Other studies (using another methods) have also indicated that individuals following a vegetarian diet reported more orthorexic behaviors than those who follow an omnivorous diet [17,34,35]. It is worth pointing out that both vegetarian diet and orthorexia nervosa share some similarities: specific food selection (consuming healthy and organic food), making eating-related issues an important area of one's own life, focusing on quality of food intake, reduction of food intake according to specific nutrition rules, nutrition rules specifying which foods are "allowed" and which are "forbidden, rigid food rules and an inability to remain flexible in one's eating habits" [20].…”
Section: Discussionsupporting
confidence: 92%
“…Zu Beginn der wissenschaftlichen Betrachtung des Phänomens ON wurden im Kontext sozio-kultureller Einflüsse Zusammenhänge mit anderen (restriktiven) Ernährungsstilen postuliert [2,12]. Während die Mehrzahl der Studien tatsächlich auf ein vermehrtes Auftreten orthorektischen Verhaltens bei Vegetariern/Veganern im Vergleich zu Nicht-Vegetariern weist [23,34,45,51,55,57,73], liefern wenige Studien auch gegenteilige Befunde mit entweder geringsten Werten bei Veganern [20] oder vergleichbare Werte zwischen verschiedenen Ernährungsstilen [50]. Aus den erwähnten Studien deutet sich als möglicher Mediator v. a. das gezügelte Essverhalten an.…”
Section: Abgrenzung Zu Anderen Verhaltensmerkmalenunclassified
“…So zeigte sich entweder kein Einfluss des Bildungsgrades bzw. Status oder leicht erhöhte Werte bei Personen mit geringerem Bildungsgrad [2,24,25,34,45,57]. Studien an Studierenden zeichnen ein leicht anderes Bild.…”
Section: äTiologie (Sozio-) Demografie Und Bmiunclassified
“…Previous studies that analyzed the occurrence and symptoms of ON have focused on the eating behaviors to some extent. The researchers first assessed ON tendency in groups following special diets, especially a vegetarian or vegan diet [22][23][24][25], and evaluated the frequency of food intake [26]. To date, other eating habits or dietary patterns (DPs) of people showing ON tendency have only been rarely studied [10,27].…”
Section: Introductionmentioning
confidence: 99%